Commodity Outlook 2003: The U.S. Economy - Peter J. van Blokland (EDIS)
According to Karl Poehl, "Americans are always worried about economic trends, suggesting that it is something of a national neurosis” (Poehl, 2002). This brief article attempts to address that neurosis.  This is EDIS document FE370, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published February 2003.